Surveillance of HIV and syphilis infections among antenatal clinic attendees in Tanzania-2003/2004 - Kabalimu Titus K; Tulli Tuhuma; Kwesigabo Gideon; Lyamuya Eligius F; Killewo Japhet; Matee Mecky IN; Somi G Geofrey R; Swai Roland O; Ng'ang'a Lucy; Isingo Raphael; Ndayongeje Joel (BMC, 2006)
Abstract Background This paper presents the prevalence of human immunodeficiency virus (HIV) and syphilis infections among women attending antenatal clinics (ANC) in Tanzania obtained during the 2003/2004 ANC surveillance. Methods Ten geographical regions; six of them were involved in a previous survey, while the remaining four were freshly selected on the basis of having the largest population among the remaining 20 regions. For each region, six ANC were selected, two from each of three strata (urban, peri-urban and rural). Three of the sites did not participate, resulting into 57 surveyed clinics. 17,813 women who were attending the chosen clinics for the first time for any pregnancy between October 2003 and January 2004. Patient particulars were obtained by interview and blood specimens were drawn for HIV and syphilis testing. HIV testing was done anonymously and the results were unlinked. Results Of the 17,813 women screened for HIV, 1,545 (8.7% (95% CI = 8.3-9.1)) tested positive with the highest prevalence in women aged 25-34 years (11%), being higher among single women (9.7%) than married women (8.6%) (p < 0.07), and increased with level of education from 5.2% among women with no education to 9.3% among those at least primary education (p < 0.001). Prevalence ranged from 4.8% (95% CI = 3.8% - 9.8%) in Kagera to 15.3% (95% CI = 13.9% - 16.8%) in Mbeya and was; 3.7%, 4.7%, 9.1%, 11.2% and 15.3% for rural, semi-urban, road side, urban and 15.3% border clinics, respectively (p < 0.001). Of the 17,323 women screened for syphilis, 1265 (7.3% (95%CI = 6.9-7.7)) were positive, with highest prevalence in the age group 35-49 yrs (10.4%) (p < 0.001), and being higher among women with no education than those with some education (9.8% versus 6.8%) (p < 0.0001), but marital status had no influence. Prevalence ranged from 2.1% (95% CI = 1.4% - 3.0%) in Kigoma to 14.9% (95% CI = 13.3%-16.6%) in Kagera and was 16.0% (95% CI = 13.3-18.9), 10.5% (95% CI = 9.5-11.5) and 5.8% (95% CI = 5.4-6.3) for roadside, rural and urban clinics, respectively. Syphilis and HIV co-infection was seen in 130/17813 (0.7%). Conclusion The high HIV prevalence observed among the ANC clinic attendees in Tanzania call for expansion of current voluntary counselling and testing (VCT) services and access to antiretroviral drugs (ARV) in the clinics. There is also a need for modification of obstetric practices and infant feeding options in HIV infection in order to prevent mother to child transmission of HIV. To increase uptake to HIV testing the opt-out strategy in which all clients are offered HIV testing is recommended in order to meet the needs of as many pregnant women as possible.